2018
DOI: 10.3996/082017-jfwm-066
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Waterfowl Carrying Capacity at Local Scales: A Case Study From Edwin B. Forsythe National Wildlife Refuge, New Jersey1

Abstract: The management of wintering North American waterfowl is based on the premise that the amount of foraging habitat can limit populations. To estimate carrying capacity of winter habitats, managers use bioenergetic models to quantify energy (food) availability and energy demand, and use results as planning tools to meet regional conservation objectives. Regional models provide only coarse estimates of carrying capacity because habitat area, habitat energy values, and temporal trends in population-level demand are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Rejecting the null hypothesis that common reed invasion per hectare into high marsh would not affect DEDs, we found that common reed would produce 509-1,743 more DEDs/ha (232-525% increase) across the five species over the 212 d of the nonbreeding season (on the basis of dabbling duck migration chronology at EBFNWR, 1 September-31 March; Ringelman et al 2018; Table 2). Further, areas converted from freshwater impoundment to common reed would produce 297-1,925 more DEDs/ha (145-654% increase) across the five species.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Rejecting the null hypothesis that common reed invasion per hectare into high marsh would not affect DEDs, we found that common reed would produce 509-1,743 more DEDs/ha (232-525% increase) across the five species over the 212 d of the nonbreeding season (on the basis of dabbling duck migration chronology at EBFNWR, 1 September-31 March; Ringelman et al 2018; Table 2). Further, areas converted from freshwater impoundment to common reed would produce 297-1,925 more DEDs/ha (145-654% increase) across the five species.…”
Section: Resultsmentioning
confidence: 81%
“…Because common reed primarily invades high marsh and freshwater impoundments, we tested the null hypothesis that common reed-invaded wetlands would not affect the energetic carrying capacity via available DEDs (per ha) as compared with noninvaded salt-marsh dabbling duck habitat. To inform DEDs, we first assumed average daily energy expenditures calculated by Livolsi (2015) (Ringelman et al 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2. Mean used food energy (millions of kcal), duck energy days (millions), and extrapolated number of ducks that could be supported for 212 days of the wintering period (based on regional dabbling duck migration chronology, 1 Sep-31 Mar; Ringelman et al 2018) Our estimates of energy supply (kcal) by wetland community type suggest that for most dabbling duck species, energy density of used foods was greater in impoundments than low marsh, high marsh, mudflat, subtidal, or quasi-tidal pool communities. Freshwater impoundments in particular tended to have the greatest energy density because they contain a large volume of energy-dense seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Ringelman et al [52] used detailed data previously collected on wintering waterfowl at Edwin B. Forsythe National Wildlife Refuge and created a local model of carrying capacity. They used 1,223 core samples collected between 2006 and 2015 to estimate food energy supply and species-specific 24-h time-activity data collected between 2011 and 2013 to estimate daily energy expenditure.…”
Section: Wintering Grounds Carrying Capacitymentioning
confidence: 99%